Pengaruh Penggunaan Media Activity Picture Cards terhadap Kemampuan Konsep Waktu pada Anak Usia 2-3 Tahun di TK Damhil - Indriyati T Husain; Icam Sutisna; Fiola Indah Putri Pratama (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
This study aims to determine the effect of using "Activity Picture Cards" on the time-concept skills of children aged 2–3 years at Damhil Kindergarten. The study employs a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The subjects consisted of 24 children aged 2–3 years at Damhil Kindergarten. Data were collected through observation, performance tests, and documentation. Data analysis included instrument validity testing using Aiken's V, inter-rater reliability testing using Cohen's Kappa, descriptive statistical analysis using the mean, and hypothesis testing using the Wilcoxon Signed-Rank Test. The study is expected to demonstrate that the use of "Activity Picture Cards" can enhance the time-concept skills of children aged 2–3 years, particularly regarding the recognition of activity sequences and the understanding of morning, midday, and night. The novelty of this research lies in the use of "Activity Picture Cards" designed to align with the developmental characteristics of 2–3-year-olds as a learning medium that is concrete, engaging, and easy to understand.